FACTORS OF MASS SPORTS AND PHYSICAL CULTURE - Haydarov Aziz Anvaryovich (Bright Mind Publishing, 2025)
The article analyzes the role of mass sports and physical culture in promoting public health, healthy lifestyle and sustaining society. Suggestions are made on ways to increase the popularity of sport, public policy and public participation in this area.
Keywords: Mass sports, physical culture, healthy lifestyle, public health, public policy.